If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + -5 = -6 Reorder the terms: -5 + X = -6 Solving -5 + X = -6 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + X = -6 + 5 Combine like terms: -5 + 5 = 0 0 + X = -6 + 5 X = -6 + 5 Combine like terms: -6 + 5 = -1 X = -1 Simplifying X = -1
| x-15=190 | | 9n+6-4n=3(n-4) | | -2(-3x+5)-7x=5(x-1)-2 | | -3s-5=5 | | 2x+10+7x-14=-x-7+14-x | | x-5y-5=0 | | -30x+20=-11x+38 | | (3x+4)2=18 | | 6-10c+1=4-4c | | 9-y=17+y | | 0=-90-45x-5x^2 | | x-6+2=-18-x | | x^4+xy^3+x^3+y^3= | | h+f=8 | | x=17+y | | n+(-4)=95 | | -13+2n+6n=1+6n | | 44=2u+14 | | .66x=15-.33x | | 19-x=172 | | 6+0.80b=0.90b | | 22x-6-18x+3=17x-3-13x+16 | | 3t*t^3=0 | | 12/3x=151/3 | | 4x^2+24x-64=o | | -8j=64 | | y-38=6(x+5) | | 2c+4-3c=-9+c+12 | | 150x+200x=14000 | | (20+2x)(30+2x)=1064 | | 2x+1=4y+7 | | 4n+0.24=14.76 |